Transnational Islam, Regional Terrorism, and Military Power: The Rise of Muslim Special Unit in the Philippines Armed Force - Bayu Mitra A. Kusuma (Journal of Southeast Asian Human Rights, 2018)
The Southern Philippines is known as one of the areas that never get out of conflict. Even in 2017 the public was shocked by the emergence of the Maute group in Marawi which affiliated with ISIS or Daesh transnational terrorists. They undertake a lot of human rights violations such as kidnapping and murder. In addition, terrorist groups that have existed before like Abu Sayyaf often operate by crossing several Southeast Asian countries waters boundary, so the problem is transformed into a regional issue. To face this problem, the Philippines government formed a Muslim special unit in their military power. On the one hand, it’s has a positive impact: (1) Religious and cultural approach will open up a larger dialogue space compared to a conventional military approach; (2) More adaptable and diffuse to gain local community support; and (3) Greatly facilitate coordination and cooperation with the military of Indonesia, Malaysia, and Brunei Darussalam as a country with Muslim majority population. But on the other hand, it’s also has a negative impact: (1) Potential emergence of factions within the military or gap between the Muslim units with other soldier; and (2) Reinforcing the stigma that Muslims are terrorists and must be fought with hard-core Muslim behind military uniform.